2011
DOI: 10.1111/j.1474-9726.2011.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular aging leads to functional heterogeneity of hematopoietic stem cells: a modeling perspective

Abstract: SummaryHematopoietic stem cells (HSCs) are the source for the lifelong supply of functional cells in peripheral blood while they simultaneously maintain their own reserve pool. However, there is accumulating evidence that HSCs are themselves subject to quantitative and qualitative exhaustion. Although several processes linked to mitotic activity can potentially account for the observed aging phenomena (e.g., DNA damage, telomere shortening, epigenetic modification), a precise understanding of HSC exhaustion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…We chose the ABM for HSC introduced by Roeder and Loeffler [26] to replace the stem cell compartment of our ODE for two reasons: it represents the stem cell population in a highly structured way (two niches, affinity, cell cycle) and has been proven successful in a broad range of scenarios relevant for clinical applications such as Imatinib-treatment of chronic myeloid leukemia in humans [30,32]. Replacement is performed on the basis of a difference equations formulation of the ABM proposed by Kim et al [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the ABM for HSC introduced by Roeder and Loeffler [26] to replace the stem cell compartment of our ODE for two reasons: it represents the stem cell population in a highly structured way (two niches, affinity, cell cycle) and has been proven successful in a broad range of scenarios relevant for clinical applications such as Imatinib-treatment of chronic myeloid leukemia in humans [30,32]. Replacement is performed on the basis of a difference equations formulation of the ABM proposed by Kim et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…In one of these two GE, which can be interpreted as a stem cell niche [24], the stem cells are quiescent and regenerate their ability to remain in the niche, while in the other GE they proliferate and lose this niche affinity. The broad range of successful applications of this modeling concept includes modeling of clonal competition [27,28], age-dependent repopulation potential after irradiation [29] and treatment of chronic myeloid leukemia with Imatinib and interferon-α [30-32]. …”
Section: Introductionmentioning
confidence: 99%
“…However, this study brings up an interesting premise that warrants further investigation: cellular heterogeneity. Cellular heterogeneity plays an important part in dictating cell function—that is, how cells process information and respond to perturbations (76, 77). Although often neglected in aging studies, heterogeneity can be dictated by many factors, in vitro and in vivo, from both cell-intrinsic and cell-extrinsic factors, such as stochasticity in cellular morphogenesis, the cell-cycle state, cell–cell and cell–matrix interactions, genetic predispositions, lifestyle (factors such as nutrition or diet, and exercise), and environmental factors and exposures.…”
Section: Aging and Cell Mechanicsmentioning
confidence: 99%
“…Transplantation is thought accelerate replicative senescence by requiring transplanted cells to rapidly proliferate to repopulate the recipient host. Mathematical models have suggested that this type of HSC exhaustion would take several life-times under homeostatic conditions and would not be relevant to normal ageing, but could contribute to anaemia in subset of patients who experienced extensive haematopoietic demands over a lifetime (Glauche, et al 2011). …”
Section: Putative Causes Of Anaemia In Older Adultsmentioning
confidence: 99%